Œil pour œil : l’art contre la technopolice - Jean-Paul Fourmentraux (Appareil)
At the frontier of digital arts, philosophy of techniques and the resolutely critical “surveillance studies”, this article proposes the ethnography of a controversy, aesthetic and political, which occurred on the occasion of the exhibition of Capture, a project of the Italian artist Paolo Cirio (2020), and of the European petition it inaugurated online, aiming at banning facial recognition in the public space. In the light of Vilem Flusser’s theories, we analyze the ambivalence of digital images in the age of facial recognition or artificial intelligence, their socio-technical determinisms, as well as the conditions and modalities of their possible reversal (or detour of their devices) through artistic ruse. We will show how the art of digital disobedience invites to “bite the machine”, to reopen the black boxes and to reverse the roles of the watchers and monitored in connection with the debate around police violence and the ambivalence of the “global security” law project.